THE ROLE OF LINGUOCULTUROLOGY IN THE FORMATION AND DEVELOPMENT OF TOURISM TERMINOLOGY (International Congress on Economics, Management and Business Studies, 2026)
This article analyzes the role of linguoculturology in the formation and development of tourism terminology based on a comprehensive scientific approach. Tourism terminology is examined as a product of the interaction between language and culture, and its semantic, pragmatic, and cognitive features are revealed. The factors influencing the formation of terms, their national-cultural characteristics, and their importance in global communication are substantiated. In addition, the theoretical and practical aspects of developing tourism terminology based on a linguoculturological approach are scientifically discussed.
Keywords: Tourism, term, linguoculturology, culture, semantics, communication, system.